Risks perceptions and willingness-to-pay for organic fresh chicken in Argentina - Lacaze, María Victoria (2009)
In developed countries, a series of food scares and the overuse of antibiotics in animals have increased consumers' concerns about chicken meat quality since the last decades. In Argentina, consumers are clearly becoming oriented to alternative chicken varieties they conceive as "healthier", "tastier" and "free of harmful chemical substances". This paper aims to calculate Argentinean consumers' willingness-to-pay (WTP) for organic fresh chicken in the domestic market by applying the Contingent Valuation approach and with a view to providing some useful insights to promote organic chicken production and consumption. A binomial logit model was estimated with data from a consumer survey conducted in Buenos Aires City, Argentina. Willingness-to-pay is explained by the consumption of organic products, health risks perceptions, production processes and regulation concerns and labels reading. WTP calculation reveals a mean value of 21.4%/kg and a median of 19%/kg. Even though both measures are below than the average price premium prevailing at the sampled stores (24.6%/kg), they are indicating that organic chicken is positively valued. In fact, it is provided with the nutritional and product origin information that consumers require and considered for them as a safer option than conventional chicken.